Initial Reports of the Deep Sea Drilling Project 1983
DOI: 10.2973/dsdp.proc.71.114.1983
|View full text |Cite
|
Sign up to set email alerts
|

An Authigenic Gypsum, Pyrite, and Glauconite Association in a Miocene Deep Sea Biogenic Ooze from the Falkland Plateau, Southwest Atlantic Ocean

Abstract: Authigenic gypsum, pyrite, and glauconite are disseminated throughout an unusually long (346 m) Miocene section of mixed biogenic carbonate and diatomaceous ooze drilled on the Falkland Plateau at DSDP Site 329 (water depth, 1519 m). The present organic carbon content of the sediment is low, ranging between 0.1 and 0.1%. Gypsum occurs as euhedral single or twinned crystals of selenite up to 5 mm in diameter, sometimes in the form of gypsum rosettes. These crystals are intact and unabraded, comprising up to 4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Gp = gypsum. grown with pyrite rods in deep sea sediments (Muza and Wise 1983). Although pseudo-hexagonal, fibrous, prismatic, and lenticular gypsum crystals may indicate dynamic soil environments in soils of southwestern Iran (Owliaie et al 2006) or in the Las Vegas basin and southern New Mexico in the U.S.A. (Buck and Van Hoesen 2002;Buck et al 2006), the variations of these crystal habits are still not comparable to those found in the hot springs of Kamchatka.…”
Section: Application To the Preservation Of Gypsum In Ancient Sedimenmentioning
confidence: 95%
“…Gp = gypsum. grown with pyrite rods in deep sea sediments (Muza and Wise 1983). Although pseudo-hexagonal, fibrous, prismatic, and lenticular gypsum crystals may indicate dynamic soil environments in soils of southwestern Iran (Owliaie et al 2006) or in the Las Vegas basin and southern New Mexico in the U.S.A. (Buck and Van Hoesen 2002;Buck et al 2006), the variations of these crystal habits are still not comparable to those found in the hot springs of Kamchatka.…”
Section: Application To the Preservation Of Gypsum In Ancient Sedimenmentioning
confidence: 95%
“…[41] The formation of gypsum crystals in marine sediments has been reported and described in only a few studies [Siesser and Rogers, 1976;Briskin and Schreiber, 1978;Muza and Sherwood, 1983;Hoareau et al, 2011]. In order to characterize the sedimentary context where gypsum might precipitate, Hoareau et al [2011] calculated the gypsum saturation index for numerous ODP/IODP cores using the available pore water data.…”
Section: Transformations Occurring During Early Diagenesismentioning
confidence: 99%
“…Calculations of gypsum saturation in several sediment cores drilled in the frame of the Ocean Drilling Program and the Integrated Ocean Drilling Program (ODP/IODP) revealed that gypsum formation in marine sediments is related either to the presence of evaporitic brines or volcanogenic material [Hoareau et al, 2011]. However, gypsum crystals have also been observed in sediments barren of evaporitic or volcanogenic material [Siesser and Rogers, 1976;Briskin and Schreiber, 1978;Muza and Sherwood, 1983]. In the study of Siesser and Rogers [1976], gypsum crystals were thought to have grown in organic-rich suboxic sediments, where low pore water pH induced by high rates of iron sulfide precipitation led to dissolution of the foraminifera.…”
mentioning
confidence: 99%
“…In pyrite grains from marine sediments Siesser (1978) found K, Si, Al, Ti, and Mg in quantities less than 0.05% by weight. Muza and Wise (1983) detected slightly higher quantities of these and Ca and Zr in sheet-like and framboidal pyrite.…”
Section: Resultsmentioning
confidence: 89%